Female firm leadership. Extent and performance in 14 EU member states - Katja Theune; Andreas Behr (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Evidence on female firm leadership is scarce and often confined to a small number of firms included in share price indices. Our large firm level data set from 2011 contains 441287 firms from 14 EU states. Based on management information, we provide evidence for the extent and the performance of female-led firms. We find strong differences in the extent of female firm leaders between the 14 states but for most countries no evidence for significant performance differences between male- and female-led firms, neither for the whole country samples nor within six broadly defined sectors. This result is confirmed when applying a matching approach to account for potential selection problems.
Keywords: J16; L25; M12; 330